2014
DOI: 10.1111/ajco.12289
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy for chronic radiation-induced tissue injuries: Australasia's largest study

Abstract: Our study demonstrates that hyperbaric oxygen therapy can be effectively used in a variety of chronic radiation-induced tissue injuries; its favorable risk profile suggests it should be considered for patients with radiation-induced tissue injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 32 publications
(76 reference statements)
0
48
0
3
Order By: Relevance
“…Summarizing all included studies, the overall response rate varied between 64.8% and 100.0% (86.4% weighted average across the studies) in studies that provided this overall response value . The CR rate varied between 20.0% and 100.0% (63.6% weighted average) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summarizing all included studies, the overall response rate varied between 64.8% and 100.0% (86.4% weighted average across the studies) in studies that provided this overall response value . The CR rate varied between 20.0% and 100.0% (63.6% weighted average) .…”
Section: Resultsmentioning
confidence: 99%
“…In the included studies, however, dental pain (due to sinus barotrauma) and vision disorder (due to eye barotrauma) were exceedingly rare, whereas otalgia (due to ear barotrauma) was more frequently reported in the included studies, and in one study even affected one‐third of the patients . It is of note that the majority of these cases include fully reversible ear barotrauma, in up to just 5% requiring myringotomy . Overall, HBOT can therefore be considered as an effective and safe treatment.…”
Section: Discussionmentioning
confidence: 97%
“…In one large Australian study, 64% of patients receiving HBOT for LSTRI who incidentally suffered xerostomia reported improvement in symptoms . Cankar et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, many prospective studies [64][65][66] and retrospective studies [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] have been performed, and the results are presented in Table 3. Results are consistent and show a generally good response rate (80 %) especially in case of a short delay between the onset of bleeding and the initiation of HBO therapy (B6 months) [70,75].…”
Section: Hyperbaric Oxygen Therapymentioning
confidence: 99%